The Effects of Hydrogen Sulfide on Adipocyte Viability in Human Adipocyte and Adipocyte-Derived Mesenchymal Stem Cell Cultures Under Ischemic Conditions. Issue 6 (December 2015) - Aykan, Andac; Ozturk, Serdar; Sahin, Ismail; Avcu, Ferit; Sagkan, Rahsan Ilikçi; Isik, Selcuk
Abstract : Background: This study evaluated the in vitro effects of hydrogen sulfide on adipocyte survival under ischemic conditions and explored possible mechanisms of its apoptotic process. Methods: The mesenchymal stem cell culture was prepared from a human subcutaneous adipose tissue sample. Adipose-derived mesenchymal stem cells were differentiated into the adipogenic direction, and a mature adipocyte culture was obtained. The adipose-derived mesenchymal stem cell and mature adipocyte cultures were both divided into 6 groups. Sodium hydrogen sulfide was used as a hydrogen sulfide donor. After treating the groups with sodium hydrogen sulfide (0, 0.1, 1, 10, 100, and 1000 μM), the cell cultures were incubated in 1% oxygen at 37°C for 24 hours. After the ischemia period, the cell culture groups were evaluated with the 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide test for the proliferation/cytotoxicity rates, flow cytometry for apoptosis and necrosis rates, and reverse transcriptase polymerase chain reaction for apoptotic (Bax, Caspase-3) and antiapoptotic (Bcl-2) gene expression levels. Results: Statistically significant increases in proliferation rates were found in mesenchymal stem cell groups treated with low dose (0, 1, and 1 μM) sodium hydrogen sulfide ( P < 0.05). For each dose, a statistically significant decrease was found in late apoptosis levels on the mature adipocyte cultures ( P < 0.05). In both cell culture groups, Bcl-2 gene expression was increased and Caspase-3 gene expression was decreased. Conclusions: Under ischemic conditions, hydrogen sulfide has a protective effect on mesenchymal stem cells and mature adipocytes, and this effect is mediated by the elevation of antiapoptotic gene expression.